DNA 5mC methylation inhibits the formation of G-quadruplex structures in the genome - Kangkang Niu; Lijun Xiang; Xiaojuan Zhang; Xiaoyu Li; Tingting Yao; Jin Li; Chu Zhang; Junpeng Liu; Yuling Peng; Guanfeng Xu; Hui Xiang; Hao Wang; et al. (Genome Biology)
Abstract Background G-quadruplex structures (G4s) have been identified in the genomes of many organisms and have been proven to play significant epigenetic regulatory roles in gene transcription. Intriguingly, only a small portion of the predicted G4-forming sequences can fold into G4s under cellular conditions. Here, we employ publicly available data, methylation inhibitors, DNA methyltransferase 1 (DNMT1) knockout, and multiple ‘Omics’ technologies to study the interplay between DNA methylation and chromatin accessibility on G4 formation and the impact on gene expression. Results We find an antagonistic correlation between genomic 5mC DNA methylation level and G4 abundance. The abundance of genomic G4s significantly increases when the genome-wide methylation level is reduced by methylation inhibitor treatment or DNMT1 knockout. The increase in G4 signals in DNMT1 knockout cells is reversed by DNMT1 overexpression. Combined ATAC-seq, whole genome bisulfite sequencing, and G4 CUT&Tag analyses demonstrate that 5mC DNA methylation inhibits G4 formation in both open and closed chromatin states. The inhibitory effect of 5mC modification on the formation of G4s is verified by circular dichroism and electrophoretic mobility shift assay in vitro. G4 CUT&Tag and RNA-seq analyses reveal that reduced DNA methylation enhances G4 formation and promotes the transcription of nearby genes. Conclusions This study demonstrates that 5mC DNA methylation directly inhibits G4 formation in the genome and modulates subsequent gene transcription, confirming the interaction between G4s and DNA methylation as an important mechanism for epigenetic regulation of gene transcription.